MON-211 Prevalence, Characteristics and Outcomes of Primary Aldosteronism in Newly Diagnosed Hypertensives in China (Pa China) - Xu, Zhixin (J Endocr Soc, 2020)
Abstract Background 44.7% adults in China have hypertension but the prevalence of primary aldosteronism (PA) in Chinese hypertensives is unknown. Objective We prospectively investigated the prevalence of PA in newly diagnosed hypertensives and tested the hypothesis that these PA patients have less severe cardiovascular complications and better outcomes when compared to those diagnosed after established (or prolonged) hypertension. Method In a community health center, consecutive hypertensive patients with an aldosterone-renin ratio≥2 (ng∙dL(−1)/mIU∙L(−1)) and plasma aldosterone concentration >10ng/dL underwent captopril challenge test and/or saline infusion test for confirmation. Adrenal CT scan and adrenal vein sampling were used for subtyping. PA patients were followed up for one year and clinical outcomes were compared with PA patients from an established hypertensive cohort. Results 1020 newly diagnosed hypertensive patients were screened over 16 months. Forty were diagnosed with PA, 948 with non-PA, resulting in a prevalence of 4.0%. Thirty-two patients were diagnosed as “possible PA” due to positive screening but failure to complete the confirmatory test. Compared to non-PA, PA patients more frequently displayed microalbuminuria (P=0.031), but the incidence of cardiovascular events was not different (P=0.927). For patients treated with surgery, complete clinical success rate was 85.7%, 28% higher than that of PA patients diagnosed after prolonged hypertension. For patients treated with medication, blood pressure control rate was 79.3%, 30% higher than that of PA patients diagnosed after prolonged hypertension. Conclusions The prevalence of PA in patients with newly diagnosed hypertension in China was at least 4.0%. PA screening in newly diagnosed hypertensive patients can lead to better clinical outcomes.